Investigation of Air Circulation For Indoor Air Quality Of Middle-Class Apartment in Jakarta, Indonesia - Nurwidyaningrum, Dyah; Ulum, Miftahul; Syamsumarno, Billy Septanto (Applied Research on Civil Engineering and Environment (ARCEE), 2020)
The most significant energy used in middle-class apartments is the air circulation unit. The use of energy from the air circulation system is related to the comfort of the user in the housing unit, so it adjusts to the applicable standard. The objection of this study is to investigate the optimization of the air circulation system in middle-class apartments in an urban area. The method is a comparative study of the government standard. The stages of the research did site observation, take air quality measurement, and interview with the questionnaire. Indoor air quality data collected are temperature, relative humidity, CO, and CO2. The data measurement compared to SNI 03-6572-2001 on Procedures for Designing Air Conditioning and Ventilation Systems in Buildings, Indonesian National Standardization.Â  The questionnaire was to find out the comfort of residents on indoor air quality (IAQ). This study reveals that almost all air quality aspects are consistent to standard, except the temperature. The results of this study that meet the criteria related to air circulation are air movement 40%, relative humidity 65.5%, air movement 40%, CO 78%, and CO2 95%. The result of the questionnaires states that 72.4% of residents feel comfortable with the air quality in the dwelling unit. The size of the room and the adequacy of ventilation in the place influences the value of the air circulation system besides air movement.